IDDF2022-ABS-0267 HLA-E/NKG2A hampers tumor surveillance of natural killer cells induced by TLR4-mediated hepatic senescence. (2nd September 2022) - Yang, Xinxiang; Man, Kwan; Ng, Kevin Tak-Pan
Abstract : Background: Hepatocellular carcinoma (HCC) recurrence occurs at a rate of 10–20% within 5 years after Liver transplantation (LT). Graft injury during LT significantly affects tumor recurrence by immunological regulation. However, the role of natural killer (NK) cells in HCC recurrence was not understood. Methods: 346 HCC patients who underwent LT were recruited. The correlation between NKG2A+NK cells and tumor recurrence was analyzed. The cytotoxic function of NKG2A+NK cells was evaluated by co-culture with HCC cells by LDH assay. Hepatic ischemia-reperfusion injury plus major hepatectomy (IRI+Hx) in C57bl/6 mice was established. Tumor cells (Hepa 1–6) were injected into the liver via the portal vein. Results: GWR (the ratio of graft volume to estimated liver volume) < 60% was an independent risk factor for early tumour recurrence after LT (IDDF2022-ABS-0267 Figure 1). The frequencies of circulating and intra-graft NK cells were lower in GWR < 60% patients post-LT (IDDF2022-ABS-0267 Figure 2). NK cells in GWR < 60% patients expressed lower Granzyme B and IFN-γ, whereas higher inhibitory marker NKG2A (IDDF2022-ABS-0267 Figure 3A, IDDF2022-ABS-0267 Figure 3B), along with increased expressions of its ligand HLA-E and inflammatory signatures. HLA-E was significantly correlated with TLR4 (IDDF2022-ABS-0267 Figure 3C). The cytotoxic function of NKG2A+NK cells was significantly decreased as they expressed lower activating markers and decreased cytokines (IDDF2022-ABS-0267 Figure 4A). When co-cultured with HCC cells, NKG2A+NK cells were with less cytotoxicity (IDDF2022-ABS-0267 Figure 4B). In IRI+Hx mouse model, liver-resident NK cells shifted to liver infiltrated NK cells after IRI+Hx, with increased expressions of NKG2A on NK cells and hepatic HLA-E mRNA (IDDF2022-ABS-0267 Figure 5A). After tumor cell injection, NKG2A+ liver-resident NK cells were increased in IRI+Hx group compared to the controls (IDDF2022-ABS-0267 Figure 5B). Senescent hepatocytes were significantly induced after hepatic IRI+Hx (IDDF2022-ABS-0267 Figure 6A). Furtherly, upregulation of NKG2A on NK cells was induced by co-cultured with senescent hepatocytes (IDDF2022-ABS-0267 Figure 6B). Conclusions: Activation of TLR4 signaling during hepatic IRI promoted cell senescence with HLA-E upregulation, inducing tumor immune escape via NKG2A-mediated inhibition of NK cells.